Prednisolone Prophase for a Week Versus Upfront Multiagent Chemotherapy in Childhood Acute Lymphoblastic Leukemia: An Analysis With Reference to Induction Mortality in a Developing Country. Issue 3 (April 2020) - Jabbar, Naeem; Mansoor, Neelum; Nadeem, Kishwer; Maqsood, MSc, Sidra; Butt, Zainab; Ashraf, Shamvil
Abstract : In childhood acute lymphoblastic leukemia, high treatment-related mortality, especially in the induction phase of treatment, is a major challenge for developing countries. The reasons are multifactorial, including a late presentation with higher disease burden, malnourishment, and limited support services. These factors may aggravate the toxic effects of upfront multiagent chemotherapy in terms of severe neutropenic sepsis and tumor lysis. Therefore, instead of upfront chemotherapy, we offered prednisolone prophase for 1 week with the objective of balancing the antileukemic versus the toxic effect of treatment. The data of 538 patients who received induction with this approach (cohort B) are compared for induction mortality with previous records of 438 patients (cohort A) treated with upfront chemotherapy. In the presence of similar clinical characteristics including age, sex, risk group, and phenotype in both cohorts, a significant difference was found in overall induction mortality of 9% in cohort B versus 14% in cohort A ( P <0.05). This difference was also significant in the high-risk and T-cell phenotype, which strengthens our hypothesis that patients with higher burden of disease may experience more fatal toxic effects with upfront intensive chemotherapy. Therefore, we suggest that the prednisolone prophase approach is beneficial to control the disease with less severe toxic effects in our settings.